THE IMPACT OF DIGITAL PLATFORMS ON THE TURNOVER OF CULINARY MSMES IN THE TONDO AGGLOMERATION AREA - Jumriani; Nurnaningsih; Patta Tope; Rita Yunus; Ika Rafika (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The low use of digital platforms by MSMEs results in limited market access and hinders revenue growth. Therefore, it is important to research the role of digitalization in increasing MSMEs' turnover. The purpose of this study is to analyze the impact of the use of digital platforms on increasing the turnover of MSMEs in the culinary sector in Tondo Village, Palu City. Using a quantitative method by collecting primary data from 95 MSME actors and analyzing it using multiple linear regression with a semi-log model through Ordinary Least Squares (OLS). The results of this study show that the use of digital platforms has a positive and significant impact on the growth of MSME turnover. On the other hand, the labor factor showed a significant negative influence, while the age of the business and initial capital did not show a significant influence. These findings show that in the era of the digital economy, the performance of MSMEs is more influenced by their ability to adapt to technology than by traditional factors. This research provides an empirical contribution by emphasizing the importance of digitalization in improving the performance of MSMEs in the context of local economic agglomeration areas.